Kepemimpinan Kepala Madrasah Dalam Upaya Meningkatkan Mutu Pendidikan Dan Kinerja Guru di MAN 1 Pati - Subaidi Subaidi (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
This research describe about the leadership of the head madrasah in improving quality of education and performance teacher at MAN 1. This kind of research is field reseach, with the design, case study. The data collection techniques through interviews, observation the questionnaire, and documentation of. As for the analysis of data used in the qualitative study conducted in an interactive and place in a continuous, to completion so that the data is saturated.Activity in, data analysis namely the reduction of, data , presentation of data the withdrawal of conclusions and verification. The research results have to conclude:  first an increase in professionalism teacher through direct strategy as the embodiment of a device for teachers, learning efforts to improve the performance of teachers and the evaluation of the learning process as well as training teachers; while coaching professionalism teacher indirectly such as include teacher in various seminars and training, a higher level of magister, including the gfc and mgmp.Both, the development of infrastructures, between pemavingan madrasah, another page the construction of a new building, and renovation of the old building, the manufacture of the fence madrasah, the construction of a mosque and madrasah, and improving the infrastructure of the multi media. Through the effort is expected to the learning process runs smoothly and potential on students. well developed. Meanwhile in the performance of teachers, peneingkatan islamic school head teacher always improve commitment in achieving discipline, motivate teachers work in intense, and the head madrasah be an example.